A Modular Algorithmic Framework for Islamic Inheritance: Integrating Formal Fiqh Principles with Edge Case Calculation - Irfanun Nisa Tsalis Hantanty; Any Meilani; Muhammad Anis; Tirto Prayitno (LP2M IAIN Palopo, 2026)
The digitization of Islamic inheritance calculation is dominated by applications focused on settling common cases (masail ammah). The majority of previous research has neither addressed nor provided solutions to specific cases of inheritance distribution. Thus, there is a challenge to develop an inheritance calculation algorithm that addresses exceptional cases within the community. This study develops a modular algorithm framework for the calculation of mawaris fiqh that includes classical mechanisms (harmony, conditions, hajb, distribution of asbabul furud and 'asobah, awl, radd, and interaction of jaddul ikhwah) so that it is not only an application of the inheritance calculator and is accompanied by a transparent pseudocode. The approach taken is normative and translates the rules of mawaris fiqh, which includes exceptional cases, into modular algorithms and object-oriented programs. The algorithm's results are then implemented and tested to ensure consistency and accuracy of the calculations. The system has been proven to be able to handle several special cases, including Umariyyatayn, awl cases, radd without 'asobah, and jaddul ikhwah complex interactions. This study contributes to the standardization of algorithms for mawaris fiqh, including classical mechanism rules with exceptional cases, an explicit modular architecture based on fiqh stages, and formal pseudocode to ensure future maintenance. This framework provides a transparent alternative to the black-box LLM trend and can be the foundation for an Islamic inheritance system algorithm that can be examined and improved.